2008
DOI: 10.1007/s11274-008-9790-7
|View full text |Cite
|
Sign up to set email alerts
|

Pyrene-degradation potentials of Pseudomonas species isolated from polluted tropical soils

Abstract: Three Pseudomonas species isolated from oil polluted soils in Lagos, Nigeria were studied for their pyrene degradation potentials. These isolates exhibited broad substrate specificities for hydrocarbon substrates including polycyclic aromatic hydrocarbons, petroleum fractions and chlorobenzoates. All three isolates tolerated salt concentrations of more than 3%. They resisted ampicillin, cenfuroxime, but susceptible to ofloxacin and ciprofloxacin. Pseudomonas sp. strain LP1 exhibited growth rates and pyrene deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 39 publications
3
29
1
Order By: Relevance
“…Also, it was noticed that the addition of 20 mg g -1 soil of plant-derived materials to soil resulted in the significantly (P0.05) higher increase in THB and crude oildegraders counts in Conocarpus-and Tamarix-amended soils compared to that when 60 and 100 mg g -1 soil of plant-derived materials were added to soil. These findings were in agreement with other studies (Al-Saleh and Obuekwe [2]; Obayori et al [11]). The identification of the crude oil-degrading bacteria revealed the predominance of Gram-negative crude oil-degrading bacteria in the unamended and amended contaminated soil samples which might be due to the higher ability of Gram-negative bacteria to adapt to crude oil pollution.…”
Section: Discussionsupporting
confidence: 94%
“…Also, it was noticed that the addition of 20 mg g -1 soil of plant-derived materials to soil resulted in the significantly (P0.05) higher increase in THB and crude oildegraders counts in Conocarpus-and Tamarix-amended soils compared to that when 60 and 100 mg g -1 soil of plant-derived materials were added to soil. These findings were in agreement with other studies (Al-Saleh and Obuekwe [2]; Obayori et al [11]). The identification of the crude oil-degrading bacteria revealed the predominance of Gram-negative crude oil-degrading bacteria in the unamended and amended contaminated soil samples which might be due to the higher ability of Gram-negative bacteria to adapt to crude oil pollution.…”
Section: Discussionsupporting
confidence: 94%
“…Based on these characteristics, it was putatively identified as Bacillus amyloliquefaciens. It is noteworthy that though, previous reports have established the propensity of PAHs degraders from the Nigerian environment (Ilori and Amund, 2000;Igwo-Ezikpe et al, 2006;Obayori et al, 2008;Salam et al, 2014), to the best of our knowledge, this is the first report of fluorene degraders from the Nigerian environment. The two isolates tolerated NaCl concentration of 7% with good and moderate growth exhibited by strain BR1 and BM1, respectively.…”
Section: Resultsmentioning
confidence: 62%
“…This physiological property favours the use of these strains as possible candidates for bioaugmentation purpose. Previous reports have shown that salinity could be a critical factor that determines the survival of allochthonous bacterial strains during bioremediation (Kästner et al, 1998;Obayori et al, 2008). In addition, the two strains resisted ceftriazone and cotrimozaxole but were susceptible to ofloxacin, gentamicin, and ciprofloxacin.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…In relation to the growth rate, the levels are much higher than those reported by Obayori et al (2008) when they studied PYR biodegradation by a Pseudomonas species isolated from polluted tropical soils (0.024 h -1 ). It is noticeable that the introduction of a mixture of the three PAHs leads to a decrease both in the maximum biomass levels and growth rate.…”
Section: Growth and Biodegradation Of Pahs In Cultures At Flask Scalementioning
confidence: 63%